The Design of a Thermoelectric Generator and Its Medical Applications - Palanisamy Mohan Kumar; Veluru Jagadeesh Babu; Arjun Subramanian; Aishwarya Bandla; Nitish Thakor; Seeram Ramakrishna; He Wei (Designs, 2019)
Growing energy demands are driving people to generate power in every possible way. New energy sources are needed to plug the energy gap. There is a growing interest in distributed energy generation due to its remarkable advantages such as flexibility, reliability, adaptability and minimal transmission losses. Thermoelectric generators (TEGs) are one such distributed power source that relies on thermal energy for electricity generation. The current review focusses on the design and optimization of TEGs to maximize the power output from the available thermal sources. The basic principle of thermoelectricity generation and suitable architecture for specific applications are explained with an overview of materials and manufacturing processes. Various cooling techniques to dissipate heat from the cold side and their influence on overall efficiency are reviewed in this work. Applications of TEGs for powering biomedical sensors have been discussed in detail. Recent advancements in TEGs for various implantable devices and their power requirements are evaluated. The exploitation of TEGs to generate power for wearable sensors has been presented, along with published experimental data. It is envisioned that this study will provide profound knowledge on TEG design for specific applications, which will be helpful for future endeavours.